Jurisdiction Of A Country’s Air Territorry In International Law Perspective - Yan Jefri Barus (Journal of Law Science, 2021)
The sovereignty of a country is no longer absolute or absolute, but at certain limits it must respect the sovereignty of other countries, which are regulated through international law. This is what became known as the relative sovereignty of the state. In the context of international law, a sovereign state must essentially obey and respect international law, as well as the sovereignty and territorial integrity of other countries. The problem in this research is How is the JURISDICTION of a country's airspace? What are the principles of air law adopted by nations in the world (internationally)? How is the JURISDICTION of a country's airspace in the perspective of international law? Its basic function is to show the way to solve research problems. The airspace contained above the land area, inland waters, and territorial sea is included in the jurisdiction of a country. This can be seen from article 1 of the Chicago Convention 1944 concerning International Civil Aviation: "State sovereignty in the air space above its territorial area is complete and exclusive sovereignity". This provision is one of the main pillars of international law governing air space. The principles of international air law include the principle of airspace sovereignty, the principle of JURISDICTION of air space, and the principle of responsibility. The principles in jurisdiction are the principle of territorial, national, passive personality, protection or security, universality, and crime according to applicable legal criteria. In relation to state jurisdiction in airspace, very closely related to law enforcement in the airspace. With jurisdiction, the country concerned has the authority and responsibility in the air to carry out law enforcement in air space.